Relationship between values and culture and suicide of the people in Lamphun province - Anusak, Bussaba (Biomedical Sciences and Clinical Medicine, 2017)
Objective To study relationship between values and culture and suicide of the people in Lamphun province. Method This research is quantitative research. selection a purposive sampling with direct relatives of 61 suicides and community / village health volunteers, residents of 122 suicides in 8 districts of Lamphun province total 183 samples were collected by questionnaire. Data were analyzed by the statistical package for social science. Results Values and cultures related to suicide among people in Lamphun include: Behavior of persons with dislike personality, Stress disorder, Psychosis, The person can not adapt to the people in the community, Do not participate in community activities and include factors such as Incompatible with colleagues, Not satis fi ed with what they have, Failure to work, Working pressure, The pressure caused by the illegal etc. Conclusion Values and cultures, both social and personal. It is an important factor in relation to suicides of the people in Lamphun province. Therefore, the development of family institutions to be strong. It is an urgent priority to prevent and alleviate suicide in society.